Education Through Ownership of the JKN (National Health Insurance of Indonesia) Mobile Application - Angraini, Wulan; Yanuarti, Riska; Samidah, Ida; Henni Febriawati; Zulaikha Agustinawati (Jurnal Kesehatan Prima, 2025)
JKN Mobile is an application presented by BPJS Health to make it easier for users to register, change and find membership data, obtain first-level health facility services and advanced-level referral facilities and make it easier for users to provide criticism or suggestions. The development of information and communication is currently growing. Likewise, health insurance requires the application of information and communication technology. The JKN mobile application is a digital transformation of BPJS health, which was originally an administrative function carried out in branch offices or health facilities, transformed into an application that can be used by application users which participants can use anywhere and at any time to improve health services in health facilities. This type of research used observational research where the researcher only makes direct observations of the variables studied without providing treatment. The data collection used is a quantitative method using a cross sectional design.The sampling technique uses the 2 Proportion Test technique with 106 people in Public Health Centre of Ujan Mas Kepahiang. Data analysis used multivariate multiple logistic regression. the research showed the majority people not having ownership JKN mobil 69,8%, aged 31-50 years 47.2%, female gender 60.4%, primary school education 42.5%, farmer occupation 62.3%, marital status amounted to 88.7%, income below the minimum wage 67.0%, law of knowledge 59.4%, negative attitudes amounted to 66.0% and mobile phone infrastructure amounted to 90.6%. analysis multivariave with multiple logistic regression showed the most influencing factor in ownership of the JKN mobile application was education, meaning theat people higher education would have a JKN mobile application of 2.266 (95% CI 1.341 – 3.828) compared to people with basic educaion after controlling for the variables of occupation, marital status and income. It can be concluded that education has an influence on ownership of the JKN mobile application on BPJS Health participants